Activation of Intercellular Adhesion Molecule 1 Expression by Helicobacter pylori Is Regulated by NF-κB in Gastric Epithelial Cancer Cells - Mori, Naoki (American Society for Microbiology, 2000)
Interactions between leukocytes and epithelial cells may play a key role in Helicobacter pylori-associated gastric mucosal inflammation. This process is mediated by various cell adhesion molecules. The present study examined the molecular mechanisms leading to H. pylori-induced epithelial cell intercellular adhesion molecule-1 (ICAM-1; also called CD54) expression. Coculture of epithelial cells with cytotoxin-associated gene pathogenicity island-positive (cag PAI(+)) H. pylori strains, but not with a cag PAI(−) strain or H. pylori culture supernatants, resulted in upregulation of steady-state mRNA levels and cell surface expression of ICAM-1. Coculture with H. pylori induced an increase in luciferase activity in cells which were transfected with a luciferase reporter gene linked to the 5′-flanking region of the ICAM-1 gene. H. pylori activated the ICAM-1 promoter via the NF-κB binding site. An inducible nuclear protein complex bound to the ICAM-1 NF-κB site and was identified as the NF-κB p50–p65 heterodimer. H. pylori induced the degradation of IκB-α, a major cytoplasmic inhibitor of NF-κB, and stimulated the expression of IκB-α mRNA. Pretreatment of epithelial cells with pyrrolidine dithiocarbamate, which blocks NF-κB activation, inhibited H. pylori-induced ICAM-1 expression. THP-1 macrophagic cells, peripheral blood mononuclear cells, and purified neutrophils adhered to H. pylori-infected epithelial cells to a greater extent than to uninfected cells. These results show that H. pylori directly induces expression of ICAM-1 on gastric epithelial cells in an NF-κB-dependent manner that may support leukocyte attachment during inflammation.